(untitled) (American Journal of Management, 2022)
Consumers continue adopting healthcare technology, from wearable devices to patient portals to telehealth. Researchers must endeavor to understand how this technology impacts behavior and health perceptions. The hypothesis is technology helps individuals to better understand, track, and interact with their health. Objectives include identifying if wearable technology impacts health consciousness, understanding digital patient portal usage, ascertaining if digital prescriptions are considered valuable, and identifying if telehealth is viewed as effective. A literature review informed the qualitative survey and exploratory focus group research. The study revealed positive sentiment towards new technology and strong consumer influence, supporting the need for additional research.